Multicarrier Spread Spectrum Communication Scheme for Cruising Sensor Network in Confined Underwater Space - Yuan Wang; Zhoumo Zeng; Yibo Li; Jinsheng Zhang; Shijiu Jin (International Journal of Distributed Sensor Networks)
A cruising sensor network works as an online monitoring system for industrial liquid environments such as oil tanks and nuclear storage ponds. The cruising sensor network consists of a few submerged nodes which can actuate themselves to execute tasks like “cruising.” This paper presents a multicarrier spread spectrum scheme, which is designed for communications between the nodes and the control station. Although underwater acoustic communication has been widely researched due to the growing demands from ocean development and marine research, communication in confined underwater space is an unexplored domain as most research focuses on communication in spacious water areas. The occasions that the cruising sensor network works in are confined. The main distinction in confined underwater spaces is the existence of strong multipath arrivals reflected by the boundaries, which can cause more severe intersymbol interference (ISI). We propose a communication scheme which applies spread spectrum in orthogonal frequency-division multiplexing (OFDM) to address severe frequency selective fading channels. This scheme can be robust in confined underwater channels when coupled with turbo code. The simulation and experimental results prove the feasibility and reliability of this scheme. It is demonstrated that significantly better performance is achieved than that of the conventional OFDM method.